OPTIMASI KINCIR AIR TIPE UNDERSHOT: PENGARUH JUMLAH SUDU DAN KETINGGIAN MENGGUNAKAN PENDEKATAN EKSPERIMENTAL: Bahasa Indonesia - Krishna Sampurno, Carolus Borromeus; Nugroho, Oktavianus Ardhian; Erianda Putri, Regina Chelinia (Machine : Jurnal Teknik Mesin, 2024)
Electrical energy is the most needed energy today. Electrical energy has become the main thing in all aspects of human life, that's why meeting the needs of electrical energy is very important. The form of energy generation that uses renewable sources is the main thing to look for today. Several types of renewable energy can be used as renewable energy sources such as solar, wind, and water. Water energy is one of the renewable energy sources whose utilization does not have an impact on the surrounding environment. The use of waterwheels is one of the uses of water energy into microhydro power plants (PLTMH). However, not all waterwheels can be used at low heads and large discharges. Of the various types of waterwheels, the undershot waterwheel type has a simple construction, can be used at low heads and small discharges but has low efficiency. This study aimed to determine the best performance from the use of the number of blades, height, and use of the blade shape of the undershot waterwheel. From this study, it is known that the use of a semi-cylindrical blade shape can reduce the drag force of the water behind the blade which can reduce the thrust resulting from the collision of water with the front of the blade. From the study results, it was found that the best performance was achieved using the number of semi-cylindrical blade and the number of 16 blade, which was 2.19 %.